Post‐transplant lymphoproliferative disorders and other malignancies after pediatric intestinal transplantation: Incidence, clinical features and outcome. (4th June 2013) - Ramos, Esther; Hernández, Francisco; Andres, Ane; Martínez‐Ojinaga, Eva; Molina, Manuel; Sarría, Jesús; Lopez‐Santamaria, Manuel; Prieto, Gerardo
Abstract PTLDs are a well‐recognized and potentially fatal complication after intestinal transplantation. We analyzed the incidence, clinical features, and outcome in a 63 intestinal transplantation series performed in our unit between October 1999 and July 2011. Types of graft included ISB (n = 23), LSB (n = 20), and MV (n = 20). Patients were categorized into three groups of immunosuppression: I (n = 43) received basiliximab, tacrolimus, and steroids; II (n = 11) thymoglobulin and tacrolimus, and III (n = 9) alemtuzumab and tacrolimus. EBV status was serially assessed. All PTLD cases were biopsied to establish histopathological diagnosis. The incidence of PTLD was 14.2% (9/63). Median onset of PTLD after transplant was four months (range: 0.5–28), within first postoperative year in 6 (66.6%) patients. Fever was the most common symptom. Graft removal was needed in four patients (44%). The patient survival rate was 66.6% (6/9). We have not found any association between PTLD and immunosuppression regimen or transplant type. However, there was a statistical association with EBV active infection.